Hemangioendothelioma of bone in a patient with a constitutional supernumerary marker - Rogatto, Silvia Regina [UNESP]; Rainho, C. A.; Zhang, Z. M.; Figueiredo, F.; Barbieri-Neto, J.; Georgetto, S. M.; Squire, J. A. (Elsevier B.V., 1999)
A 13-year old girl was diagnosed as having a bone hemangioendothelioma. Cytogenetic studies identified the presence of a small supernumerary marker chromosome in this patient. Classical cytogenetic methods using G-, C-, Ag-NOR-banding were supplemented by spectral karyotyping (SKY) and fluorescence in situ hybridization to reveal a karyotype 47,XX,+mar.ish der(22)(D22S543+) karyotype in cells derived from the tumor and lymphocytes. These findings suggest that the supernumerary marker chromosome originated from the proximal centromeric region of chromosome 22, and that trisomy of the region 22q11: was not associated with adverse phenotypic effects, but that the presence of trisomy 22q11 may be related to the development of this tumor. (C) Elsevier B.V., 1999. All rights reserved.